First-principles study of the structural, phonon, elastic, and thermodynamic properties of Al3Ta compound under high pressure - Leini, W.; Zhang, T.; Wu, Z.; Wei, N. (Condensed Matter Physics, 2018)
We have investigated the phonon, elastic and thermodynamic properties of L1₂ phase Al₃Ta by density functional theory approach combining with quasi-harmonic approximation model. The results of phonon band structure shows that L1₂ phase Al₃Ta possesses dynamical stability in the pressure range from 0 to 80 GPa due to
the absence of imaginary frequencies. The pressure dependences of the elastic constants Ci j, bulk modulus B,
shear modulus G, Young’s modulus Y, B/G and Poisson’s ratio ν have been analysed. The elastic constants
are satisfied with mechanical stability criteria up to the external pressure of 80 GPa. The results of the elastic
properties studies show that Al3Ta compound possesses a higher hardness, improved ductility and plasticity under higher pressures. Further, we systematically investigate the thermodynamic properties, such as the Debye
temperature Θ, heat capacity Cp, and thermal expansion coefficient α, and provide the relationships between
thermal parameters and pressure. Дослiджено фононнi, пружнi та термодинамiчнi властивостi Al₃Ta у L1₂ фазi методом функцiоналу густини у поєднаннi з квазигармонiчною апроксимацiйною моделлю. Результати структури фононної зони
показують, що Al₃Ta у L1₂ фазi володiє динамiчною стiйкiстю у дiапазонi тиску вiд 0 до 80 ГПа завдяки
вiдсутностi уявних частот. Проаналiзовано тисковi залежностi Ci j, об’ємного модуля пружностi B, модуля
зсуву G, модуля Янга Y, B/G та коефiцiєнта Пуассона ν. Пружнi сталi задовольняють критерiй механiчної стiйкостi аж до зовнiшнього тиску 80 ГПа. Результати аналiзу властивостей пружностi показують, що
сполука Al₃Ta володiє вищою твердiстю, кращою тягучiстю i пластичнiстю при високих тисках. Крiм того,
систематично дослiджено такi термодинамiчнi властивостi, як температура Дебая Θ, питома теплоємнiсть
Cp та коефiцiєнт теплового розширення α, а також встановлено залежнiсть мiж тепловими параметрами
i тиском.